Artifacts in Simultaneous hdEEG/fMRI Imaging: A Nonlinear Dimensionality Reduction Approach - Piorecky, Marek; Koudelka, Vlastimil; Strobl, Jan; Brunovsky, Martin; Krajca, Vladimir (Sensors (Basel, Switzerland), 2019)
Simultaneous recordings of electroencephalogram (EEG) and functional magnetic resonance imaging (fMRI) are at the forefront of technologies of interest to physicians and scientists because they combine the benefits of both modalities-better time resolution (hdEEG) and space resolution (fMRI). However, EEG measurements in the scanner contain an electromagnetic field that is induced in leads as a result of gradient switching slight head movements and vibrations, and it is corrupted by changes in the measured potential because of the Hall phenomenon. The aim of this study is to design and test a methodology for inspecting hidden EEG structures with respect to artifacts. We propose a top-down strategy to obtain additional information that is not visible in a single recording. The time-domain independent component analysis algorithm was employed to obtain independent components and spatial weights. A nonlinear dimension reduction technique t-distributed stochastic neighbor embedding was used to create low-dimensional space, which was then partitioned using the density-based spatial clustering of applications with noise (DBSCAN). The relationships between the found data structure and the used criteria were investigated. As a result, we were able to extract information from the data structure regarding electrooculographic, electrocardiographic, electromyographic and gradient artifacts. This new methodology could facilitate the identification of artifacts and their residues from simultaneous EEG in fMRI.
Keywords: Magnetic Resonance Imaging; Nonlinear Dynamics; independent component analysis; artifact; hluk; Electrooculography; lidé; magnetická rezonanční tomografie; hdEEG; Algorithms; elektrookulografie; nonlinear dimension reduction; Artifacts; nelineární dynamika; algoritmy; fMRI; elektroencefalografie; Noise; simultaneous measurement; artefakty; Electroencephalography; Humans